High arsenic tolerance in Brevundimonas aurantiaca PFAB1 from an arsenic-rich Indian hot spring - Aparna Banerjee (Electronic Journal of Biotechnology, 2021)
Background: Arsenic contamination in the ground water of rural India is a recurrent problem and decontamination is mostly based on the chemical or physical treatments until now. Microbial bioremediation is eco-friendly, cheap, time-efficient and does not produce any toxic by-products. Result: In the present study, a high arsenic tolerant bacteria Brevundimonas aurantiaca PFAB1 was isolated from Panifala hot spring located in West Bengal, India. Previously Panifala was also reported to be an arsenic-rich hot spring. B. aurantiaca PFAB1 exhibited both positive arsenic reductase and arsenite oxidase activity. It was tolerant to arsenite up to 90 mM and arsenate up to 310 mM. Electron microscopy has proved significant changes in cellular micromorphology and stalk appearance under the presence of arsenic in growth medium. Bioaccumulation of arsenic in As (III) treated cells were 0.01% of the total cell weight, while 0.43% in case of As (V) treatment. Conclusions: All experimental lines of evidence prove the uptake/accumulation of arsenic within the bacterial cell. All these features will help in the exploitation of B. aurantiaca PFAB1 as a potent biological weapon to fight arsenic toxicity in the near future.How to cite: Banerjee A, Sarkar S, Gorai S, et al. High arsenic tolerance in Brevundimonas aurantiaca PFAB1 from an arsenic-rich Indian hot spring. Electron J Biotechnol 2021:52. https://doi.org/10.1016/j.ejbt.2021.05.006